Child Protection and Maltreatment in the Philippines: A Systematic Review of the Literature. Issue 1 (January 2017) - Roche, Steven
Abstract: To gain a better understanding of the dimensions, characteristics and phenomenon of child maltreatment and its policy responses in the Philippines, this article provides a systematic review of the peer reviewed literature. This review provides a summary and analysis of the core child maltreatment issues in the Philippines and examines child protection policy responses. It takes a systematic approach, identifying 31 peer reviewed articles from a diverse range of scholarship that met its criteria, and subjected to a quality appraisal tool. Its findings provide important details about child maltreatment and child protection arrangements in the Philippines. It recommends further research into policy and programmatic approaches to child maltreatment, a greater focus on the social, cultural and structural influences on child maltreatment, and investigation into child maltreatment, particularly child sexual abuse, in contexts outside of the home, such as in institutions.